Prevalence of Hepatitis B Virus Infection in Blood Donors Based on Titer Hepatitis B Surface Antigen Examination (HBsAg) - SUPIANA DIAN NURTJAHYANI; RETNO HANDAJANI (Microbiology Indonesia, 2019)
Hepatitis B remains a global public health problem. Infection from hepatitis B virus (HBV) can be transmitted through a blood test or a blood transfusion. This study was conducted to identify the prevalence of HBV infection in blood donors based on examination of HBsAg titers . Blood donors from Tuban Red Cross used as sample. The method used in this research is HBsAg titers examination performed by ELISA according to the procedureoutlined in the Kit. HBsAg titers positive mostly found in men. In men from 13 samples (8.67%) are HBsAg titers positive of 150 samples while in woman all negative for HBsAg titers from 137 samples. The average titer positive was 3.095 with a standard deviation of 0.187. While HBsAg titers negative have average of 0.03 with a standard deviation of 0.14. This study showed that the prevalence of HBV infection in blood donors is most numerous in men with HBsAg titers positive number of 8.67%.